Efficient quantum transport in a multi-site system combining classical noise and quantum baths. (20th January 2020) - Kurt, Arzu; Rossi, Matteo A C; Piilo, Jyrki
Abstract: We study the population dynamics and quantum transport efficiency of a multi-site dissipative system driven by a random telegraph noise (RTN) by using a variational polaron master equation for both linear chain and ring configurations. By using two different environment descriptions—RTN only and a thermal bath+RTN—we show that the presence of the classical noise has a non-trivial role on quantum transport. We observe that there exist large areas of parameter space where the combined bath+RTN influence is clearly beneficial for populating the target state of the transport, and for average trapping time and transport efficiency when accounting for the presence of the reaction center via the use of the sink. This result holds for both of the considered intra-site coupling configurations including a chain and ring. In general, our formalism and achieved results provide a platform for engineering and characterizing efficient quantum transport in multi-site systems both for realistic environments and engineered systems.